Population Dilemmas in the Middle East : Essays in Political Demography and Economy - Gilbar, Gad G. (London Frank Cass, 1997)
This study provides a general outline of Palestinian population growth between 1948 and 1987 and then focuses on the town of Nablus for a detailed analysis of the main aspects of Palestinian migration and high rates of natural increase.
Include Tables, Map, Notes and Index
Keywords: Middle East -- Population--Economic aspects -- Population